2012
DOI: 10.1021/es302319m
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Predicting the Emission Rate of Phthalate Plasticizer from Vinyl Flooring in a Specially-Designed Chamber

Abstract: The emission of di-2-ethylhexyl phthalate (DEHP) from vinyl flooring (VF) was measured in specially designed stainless steel chambers. In duplicate chamber studies, the gas-phase concentration in the chamber increased slowly and reached a steady state level of 0.8-0.9 μg/m(3) after about 20 days. By increasing the area of vinyl flooring and decreasing that of the stainless steel surface within the chamber, the time to reach steady state was significantly reduced, compared to a previous study (1 month versus 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
161
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(169 citation statements)
references
References 37 publications
8
161
0
Order By: Relevance
“…Since several SVOCs adsorbed on the diffusive sampler it can be assumed that SVOCs are also adsorbed on the surfaces of the showcases and emission test chambers. This assumption is confirmed by workings of Xu et al (2012) and Clausen et al (2004).…”
Section: Influences On the Resultssupporting
confidence: 54%
“…Since several SVOCs adsorbed on the diffusive sampler it can be assumed that SVOCs are also adsorbed on the surfaces of the showcases and emission test chambers. This assumption is confirmed by workings of Xu et al (2012) and Clausen et al (2004).…”
Section: Influences On the Resultssupporting
confidence: 54%
“…2 Because phthalate additives are not chemically bound to the polymer matrix, they usually are emitted slowly from the products into the air or other media. 3 As a result, phthalates are ubiquitous and among the most abundant SVOCs in indoor environments. 1,4−6 Recent studies have suggested that exposure to some phthalates may cause irreversible changes in the development of the human reproductive tract; 7−13 increase the risk of asthma, rhinitis, and allergies; 4,14−18 and affect endogenous hormones.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They showed that emissions of these compounds that have very low volatility are subject to "external" control (partitioning from the material into the gas phase, the gas-phase mass-transfer coefficient, and strong sorption onto interior surfaces, including airborne particles). Using data collected in a specially designed stainless steel chamber, Xu et al 3 showed that the emission rate of di(2-ethylhexyl) phthalate (DEHP) from vinyl flooring can be predicted based on a priori knowledge of y 0 , the gas-phase concentration of DEHP in equilibrium with the material phase, the material to air and air to stainless steel-surface mass-transfer coefficients (h m ), and the stainless steel/air equilibrium relationship. Liang and Xu 30 recently improved the design of the earlier emission chamber and developed a novel, rapid method to measure y 0 for a range of phthalate compounds released from building materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Early animal studies have so far tended not to quantify the impact of lower doses and more complex combinations of factors on human health. However, when biomonitoring of concentrations of phthalate metabolites was undertaken in the general population using blood and urine, the blood results suggested that over 75% of the US population is exposed to phthalates, while for urine this was as high as 95% [75].…”
Section: Pvc Additivesmentioning
confidence: 99%